A multiple‐stimulus‐without‐replacement assessment for sexual partners: Purchase task validation. Issue 3 (14th May 2016) - Jarmolowicz, David P.; Lemley, Shea M.; Mateos, Ananya; Sofis, Michael J.
Abstract : The current study developed and tested a multiple‐stimulus‐without‐replacement (MSWO) assessment for potential sexual partners for use in research on human immunodeficiency virus. College students ( N = 41) first completed an MSWO assessment and then completed a hypothetical purchase task for encounters with partners identified by the MSWO as high, median, and low preference. Overall, hypothetical purchase task responding was consistent with that from the MSWO, in that the highest valuation was observed for the high‐preference partner and the lowest for the low‐preference partner. Potentially interesting individual differences in purchase task responding, however, were obtained; some subjects showed differentiated responding among the 3 preference levels ( n = 15), whereas others similarly valued high‐ and median‐preference partners ( n = 5), and others similarly valued low‐ and median‐preference partners ( n = 18).